Teaching, task processing - Dos Santos, Elaine Barbosa (Faculdade de Ciências e Letras - Unesp - Araraquara., 2014)
The present work aims to share with education agents the importance of the act of the teaching which goes far beyond an elementary transmission of content. Through a careful literature review and participant observation, there is an attempt to bring out the educational action as a way of desalienation, leading students to the construction of a debate about education, which is understood as a developing field of interpretations and perspectives on humans and what it would be ideal to happen to them in their distinct life cycles. An emancipator form of teaching must work towards affection, respect and the promotion of learner autonomy of this paper is to understand education as a way to change the world, overcoming the differences and promoting social harmony as well as a reflection on the education process as a key to open new doors.